Modulation of Immune Response to Chlamydia muridarum by Host miR-135a - Keck, Jonathon; Chambers, James P.; Yu, Jieh-Juen; Cheng, Xingguo; Christenson, Lane K.; Guentzel, M. N.; Gupta, Rishein; Arulanandam, Bernard P. (Frontiers in Cellular and Infection Microbiology, 2021)
Previously, our laboratory established the role of small, noncoding RNA species, i.e., microRNA (miRNA) including miR-135a in anti-chlamydial immunity in infected hosts. We report here chlamydial infection results in decreased miR-135a expression in mouse genital tissue and a fibroblast cell line. Several chemokine/chemokine receptor genes (including CXCL10, CCR5) associated with chlamydial pathogenesis were identified in silico to contain putative miR-135a binding sequence(s) at 3’ untranslated region. The role of miR-135a in the host immune response was investigated using exogenous miR-135a mimic to rescue the immune phenotype associated with miR-135a deficiency following Chlamydia muridarum (Cm) infection. We observed miR-135a regulation of Cm-primed bone marrow derived dendritic cells (BMDC) via activation of Cm-immune CD4+ T cells for clonal expansion and CCR5 expression. Using a transwell cell migration assay, we demonstrate the role of miR-135a in regulating genital tract cell CXCL10 expression and recruitment of CXCR3+ CD4+ T cells via the CXCL10/CXCR3 axis. Collectively, data reported here support the multifaceted role of miR-135a in immune regulation in response to chlamydial infection.